Answer:
h = b = 866.025 m or 866.03 rounded
Step-by-step explanation:
Sides:
a = 1000 m
b = 866.025 m
c = 500 m
Angles:
A = 90 °
B = 60 °
C = 30 °
Other:
P = 2366.03 m
s = 1183.01 m
K = 216506 m²
r = 183.013 m
R = 500 m
Agenda: A = angle A
B = angle B
C = angle C
a = side a
b = side b
c = side c
P = perimeter
s = semi-perimeter
K = area
r = radius of inscribed circle
R = radius of circumscribed circle
-4(w +1) = -24
W=
Answer:
w = 5
Step-by-step explanation:
-4(w + 1) = -24
(w + 1) = -24/-4
(w + 1) = 6
w = 6 - 1
w = 5
*negative ÷ negative = positive*
5 cm
20 cm
10 cm
15 cm
Answer:
20 cm
Step-by-step explanation:
each side of each triangle is 5. You can label all of the sides. They'll each be 5.
5 + 5 + 5 + 5 = 20
The expression that gives the new amount he will pay from the purchase that Gabriel made at the grocery store is 2.5x + 2y - $2
Word problems in mathematics involve a careful understanding and interpretation of the variables given. This is because it is from these variables we will compute an equation to solve the word problem.
In this question, we are being told that:
So, the total amount of apples and lettuce bought is:
Total amount to be paid = 2.5x + 2y.
However, he had a coupon for $2 off his total bills. It implies the new amount he will pay will be:
New amount = 2.5x + 2y - $2
Learn more about word problems here:
#SPJ5
Answer:
D is the answer.
Step-by-step explanation:
2y + 2.5x-2
5 ways
97 ways
25 ways
Q=-7a^2-3ab+5b^2
P-Q
Answer:
3a² + ab + 4b²
Step-by-step explanation:
Combine like terms. Like terms have same variable with same power.
P - Q = -4a² - 2ab + 9b² - (-7a² - 3ab + 5b²)
To open the brackets, multiply each term of Q by (-1)
= -4a² - 2ab + 9b² + 7a²+ 3ab - 5b²
-4a² and 7a² are like terms.
(-2ab) and 3ab are like terms.
9b² and (-5b²) are like terms.
= -4a² + 7a² -2ab + 3ab + 9b²- 5b²
= 3a² + ab + 4b²
Answer:
3a² + ab + 4b²
Step-by-step explanation:
P - Q
= - 4a² - 2ab + 9b² - (- 7a² - 3ab + 5b² ) ← distribute parenthesis by - 1
= - 4a² - 2ab + 9b² + 7a² + 3ab - 5b² ← collect like terms
= 3a² + ab + 4b²